Distribution of FDG-avid nodes in esophageal cancer: implications for radiotherapy target delineation. Issue 1 (December 2016) - Garcia, Brandon; Goodman, Karyn; Cambridge, Lajhem; Dunphy, Mark; Wu, Abraham
Abstract Purpose Clinical target volumes (CTV) for radiotherapy (RT) in esophageal cancer (EC) are based on standard expansions of primary tumor volume. Data is needed to define regions at highest risk for occult disease, based on histology and location of the primary tumor. We therefore reviewed PET scans in EC patients to characterize the location of FDG-avid lymph node metastases (LNM). Materials and methods We identified 473 EC patients with reviewable pre-treatment PET-CT scans. Tumors were classified by histology and location; 85% were distal or GE junction tumors and 71% were adenocarcinoma. FDG-avid LNM were classified using standard radiographic nodal atlases, and distances from primary tumor to paraesophageal LNM were also measured. Results The most common LNM in upper EC were supraclavicular, retrotracheal and paratracheal. The most common LNM in lower EC were paraesophageal and in the gastrohepatic space. Overall, 55% of paraesophageal LNM were adjacent to primary tumor. Of upper esophageal tumors with paraesophageal LNM, 87% were adjacent to the tumor and none were >6 cm from tumor. However, 57% of lower esophageal tumors with paraesophageal LNM had non-adjacent paraesophageal nodes, 24% of which were >8 cm from the tumor. Conclusion A more data-driven and individualized approach to CTV delineation could improve the therapeutic ratio of RT in esophageal cancer. These results can guide CTV delineation by indicating the potential distribution of nodal involvement in esophageal cancer.